The Reception of the Book of the Watchers in Valentinus’s Fragment 1 (Clement of Alexandria, Stromata II.36.2–4) - Berno, Francesco (Gnosis, 2023)
The article intends to argue in favor of the dependence of Valentinus’s Fragment 1 (Clement, Strom. 2.36.2-4) on the Greek text of the Book of the Watchers. Moving from Valentinus’s recourse to specific expressions of the latter – and in particular of his “technical” use of the term φόβος (“fear”) and of the verb ἀφανίζω (“to destroy”; “to disfigure”) – the aim is to throw new light not only on the origin of Valentinus’s anthropogonic narrative, but also on the reasons and the limits of the re-use of Enochian material in the extant Valentinian production.